Hubungan Pemberian Makanan Pendamping ASI Dini dengan Kejadian Diare pada Bayi Usia Kurang 6 Bulan di Wilayah Kerja Puskesmas Grabag II Kabupaten Magelang Tahun 2013 - Evy Ernawati; Siti Fadhilah; Solikatun Solikatun (Journal of Health (JoH), 2015)
Background : Diarrhea is one of the major health problems in development countries , including Indonesia . babies get Complementary feeding ( MP - ASI ) before the age of 6 months , more diarrhea , constipation , cough , runny nose , and heat than infants who are solely breastfed exclusively and get Complementary feeding ( MP - ASI ) in a timely manner . Figures achievement of exclusive breastfeeding in Puskesmas Grabag II Magelang only by 6.2 % , and the incidence of diarrhea in children aged 0-6 months were 43 events. Objective: Given the relationship between giving Premature Complementary feeding the incidence of diarrhea in infants aged less than 6 months in Puskesmas Grabag II Magelang Regency in 2013. Methods: This study is the analytic survey research , using a cross-sectional survey design . The sampling technique used is stratified random sampling proportional to the number of samples in this study were 68 respondents. Results : There is a relationship between the provision of Early Complementary feed the incidence of diarrhea in infants aged less than 6 months in Puskesmas Grabag II Magelang Regency in 2013 with strong ties (0.588).